Evaluation of the methodology in publications describing epidemiological design for dental research: a critical analysis - Telmo Oliveira Bittar (RSBO Revista Sul-Brasileira de Odontologia, 2011)
Introduction and objective: To describe, analyze, and critically review the methodology employed in dental epidemiological research available on electronic databases, evaluating their structures according to Strobe and Consort initiative. Material and methods: ISI Web of knowledge, Scopus, and Pubmed electronic databases were selected for literature research, gathering publications in dental epidemiological area using the following designs: cross-sectional, cohort, case-control, descriptive, experimental, and quasi-experimental. Subsequently, five specific dentistry journals were selected and had their abstracts content analyzed under Strobe and Consort statement criterion. Results: From a universe of 10,160 articles from Pubmed (the greatest number), only 3,198 could be classified according to their epidemiological design by the electronic database searching tool. The most common designs were cross-sectional, cohort, case-control, descriptive, experimental and quasi-experimental publications, showing a tendency towards occurring bias and confounding factors in literature research due to missing words in papers structure. Even though Consort and Strobe initiatives have been accomplished since 2001 and 2004 respectively, some publications are not suitable for their checklist. Conclusion: Consort and Strobe statements must be strengthened by dental journals, editors and reviewers to improve the quality of the studies, attempting to avoid any sort of bias or confounding factors in the literature research performed by electronic database.